filmov
tv
Prove that sinA/cotA+ cosecA - sinA/cotA-cosecA = 2
Показать описание
sinA/cotA+ cosecA - sinA/cotA-cosecA = 2
cota-tana=2cos2a-1/sinacosa
1/coseca-cota-1/sina=1/sina-1/coseca+cota
(sina+cosa)(seca+coseca)=2+seca coseca
cota+coseca-1/cota-coseca+1=1+cosa/sina
cosa/1-tana+sina/1-cota=sina+cosa
√seca-1/seca+1+√seca+1/seca-1=2coseca
1-sina/coseca+cota 1-sina/coseca+cota
prove that root seca-1/seca+1
cota-tana=2cos2a-1/sinacosa
1/coseca-cota-1/sina=1/sina-1/coseca+cota
(sina+cosa)(seca+coseca)=2+seca coseca
cota+coseca-1/cota-coseca+1=1+cosa/sina
cosa/1-tana+sina/1-cota=sina+cosa
√seca-1/seca+1+√seca+1/seca-1=2coseca
1-sina/coseca+cota 1-sina/coseca+cota
prove that root seca-1/seca+1